TAX EVASION IN SOCIO-PROFFESIONAL GROUPS (Research Bulletins of the Faculty of Economic Sciences, 2021)
Tax evasion is a term which means illegallyavoidingpaying taxes by people. This illegal practice is a seriousproblem of Polish Public Authorities. There can be some tax evasion reasons, for instance: economic, social and legal butthey can be different in socio-professionalgroups. A socio-professionalgroup may have an impact on taxpay-ers’ behavior.
Keywords: tax evasion, taxes, taxpayers, tax avoidance, tax system